2019
DOI: 10.1002/14651858.cd002295.pub6
|View full text |Cite
|
Sign up to set email alerts
|

Exercise interventions for smoking cessation

Abstract: Background Taking regular exercise may help people give up smoking by moderating nicotine withdrawal and cravings, and by helping to manage weight gain. Objectives To determine whether exercise-based interventions alone, or combined with a smoking cessation programme, are more effective than a smoking cessation intervention alone. Search methods We searched the Cochrane Tobacco Addiction Group Specialized Register in April 2014, and searched MEDLINE, EMBASE, PsycINFO, and CINAHL Plus in May 2014. Selection cri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
48
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 231 publications
3
48
0
2
Order By: Relevance
“…NICE (2013) recommendations for smoking cessation in people with mental health problems do not include physical activity as an intervention but focus primarily on pharmacotherapy and behavioural/ psychological support. Despite the well-documented links between exercise and wellbeing, previous systematic reviews have found limited evidence for the effectiveness of physical activity on smoking cessation in healthy individuals (Ussher, Faulkner, Angus, Hartmann-Boyce, & Taylor, 2019;Ussher, Taylor, West, & McEwen, 2000) and those with alcohol addiction or physical health issues (Ussher et al, 2000). Moreover, due to the lack of staff resources, and environmental or physical risk management practices in psychiatric wards (Shattell, Andes, & Thomas, 2008), exercise-focused interventions may be difficult to implement for smokers with mental health problems.…”
Section: Interventionsmentioning
confidence: 99%
“…NICE (2013) recommendations for smoking cessation in people with mental health problems do not include physical activity as an intervention but focus primarily on pharmacotherapy and behavioural/ psychological support. Despite the well-documented links between exercise and wellbeing, previous systematic reviews have found limited evidence for the effectiveness of physical activity on smoking cessation in healthy individuals (Ussher, Faulkner, Angus, Hartmann-Boyce, & Taylor, 2019;Ussher, Taylor, West, & McEwen, 2000) and those with alcohol addiction or physical health issues (Ussher et al, 2000). Moreover, due to the lack of staff resources, and environmental or physical risk management practices in psychiatric wards (Shattell, Andes, & Thomas, 2008), exercise-focused interventions may be difficult to implement for smokers with mental health problems.…”
Section: Interventionsmentioning
confidence: 99%
“…There is broad interest in the role of physical activity (PA) as a treatment and reduction strategy for alcohol and other drug use ( Taylor, Oh, & Cullen, 2013 ; Volkow, 2011 ) and in how physical activity can be used to influence other health behaviours ( Taylor, 2014 ; Thompson, Lambert, Greaves, & Taylor, 2018 ; Ussher, Faulkner, Angus, Hartmann-Boyce, & Taylor, 2019 ). Physical activity interventions could impact on the prevention, reduction, and treatment of alcohol and other drug use but previous reviews have been conceptually confusing and methodologically weak.…”
Section: Introductionmentioning
confidence: 99%
“…The link between smoking and body weight is closely related and poses significant challenges for researchers investigating intervention effects in smokers. The most recent Cochrane review of 24 trials with a total of 7279 adult participants investigated the effectiveness of exercise-based interventions alone, or combined with a smoking cessation programmes and concluded no significant effect from adding exercise to smoking cessation [22]. The same authors do state and concludes that more studies are needed and that future trials may alter these conclusions [22].…”
Section: Introductionmentioning
confidence: 99%
“…The most recent Cochrane review of 24 trials with a total of 7279 adult participants investigated the effectiveness of exercise-based interventions alone, or combined with a smoking cessation programmes and concluded no significant effect from adding exercise to smoking cessation [22]. The same authors do state and concludes that more studies are needed and that future trials may alter these conclusions [22]. Moreover, new research published in the British Journal of Pharmacology has confirmed that exercise can help smokers quit smoking and may aid smoking cessation by reducing the severity of smoking withdrawal symptoms [23].…”
Section: Introductionmentioning
confidence: 99%